Postrace Dry Needling Does Not Reduce Subsequent Soreness and Cramping—A Randomized Controlled Trial. Issue 3 (May 2021) - Cushman, Daniel M.; Cummings, Keith; Skinner, Lee; Holman, Anna; Haight, Peter; Brobeck, Matthew; Teramoto, Masaru; Tang, Chi
Abstract : Objective: To identify whether a single session of postrace dry needling can decrease postrace soreness and quantity of postrace leg cramps in half-marathon and full-marathon runners. Design: Single-blind, prospective, randomized, controlled trial. Setting: Finish line of 2018 Salt Lake City Marathon & Half-Marathon. Participants: Runners aged 18 years or older who completed a marathon or half-marathon. Interventions: True or sham dry needling of the bilateral vastus medialis and soleus muscles within 1 hour of race completion by 2 experienced practitioners. Main Outcome Measures: The primary outcome measure was numeric pain rating improvements for soreness on days 1, 2, 3, and 7 compared to immediately postrace. Secondary outcome measures included number of postrace cramps and subjective improvement of soreness. Results: Sixty-two runners were included with 28 receiving true and 34 receiving sham dry needling. Objective pain scores showed an increase in pain of the soleus muscles at days 1 and 2 ( P ⩽ 0.003 and P ⩽ 0.041, respectively) in the dry needling group. No differences were seen in postrace pain in the vastus medialis muscles ( P > 0.05). No association was seen between treatment group and presence of postrace cramping at any time point ( P > 0.05). Subjectively, there was a nonsignificant trend for those receiving dry needling to feel better than expected over time ( P = 0.089), but no difference with cramping ( P = 0.396). Conclusions: A single postrace dry needling session does not objectively improve pain scores or cramping compared to sham therapy. Abstract : Supplemental Digital Content is Available in the Text.